THE INFLUENCE OF TRANSPARENCY, ACCOUNTABILITY, SUPERVISION, AND HR COMPETENCE ON APBD MANAGEMENT AT BPKAD SURABAYA CITY - Mahadevi Pramudyawardhani; Munari Munari (International Journal of Economy, Education and Entrepreneurship, 2023)
Realizing information disclosure to the public about government accountability reports comes with several potential negative consequences. As a result, this study aims to investigate and demonstrate how the management of the Regional Revenue and Expenditure Budget (APBD) is affected by factors such as transparency, accountability, supervision, and the competence of human resources. The population in this study were Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD) Surabaya employees. This study uses quantitative methods and primary data. Purposive sampling became the sampling technique in this study. Data analysis techniques use the Statistical Program for Special Science (SPSS). According to the findings of this research project, there is evidence that openness, responsibility, and oversight impact how the Regional Revenue and Expenditure Budget (APBD) is managed. In the meantime, it has been determined that the competence of human resource management has little impact on managing the Regional Revenue and Expenditure Budget (APBD).